A Disease of Dignity - Stevens, James K.A. (Ars Medica, 2018)
This is a non-fiction narrative of dealing with a rare neurological disesse called idiopathic hypersomnia, in addition to depression and generalized anxiety disorder. I recount from when I first began noticing symptoms of these disorders, through diagnosis and treatment, to the present. I emphasize the damage of these diseases to my personal and academic life, relationships, and self esteem.